2017
DOI: 10.1016/j.resourpol.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Surface-strip coal mine land rehabilitation planning in South Africa and Australia: Maturity and opportunities for improvement

Abstract: Highlights • A maturity model for surface-strip coal mine land rehabilitation planning is presented • The model was applied to mine rehabilitation guidelines and approval reports • Guidelines and approval reports are vulnerable to adequate, but not yet resilient • Legislation may be contributing to immaturity for some aspects of planning • Upfront planning and analysis in dynamic mining environments are discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…When left for extended periods, these discard dumps tend to be a source of air pollutants and, following precipitation leach metal ions from the carbonaceous material into waterways that may lead to acid rock drainage and contamination of recipient water courses and streams (Claassens et al 2006). Land devastation in regions where coal mining has taken place is well documented and serves to emphasise the need for continued effort to develop sound rehabilitation technologies to support re-vegetation and transformation of this disturbed land to a new beneficial condition (Sheoran et al 2010;Limpitlaw and Briel 2015;Weyer et al 2017). Biological rehabilitation has become the strategy of choice and is considered to be economic, safe, more energy efficient and environmentally compatible, and potentially capable of providing a means to convert coal discard to ash and sulphurfree products of value (Reich-Walber et al 1997;Klein et al 2001;Hofrichter and Fakoussa 2001;Machnikowska et al 2002;Sekhohola et al 2013;Cowan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When left for extended periods, these discard dumps tend to be a source of air pollutants and, following precipitation leach metal ions from the carbonaceous material into waterways that may lead to acid rock drainage and contamination of recipient water courses and streams (Claassens et al 2006). Land devastation in regions where coal mining has taken place is well documented and serves to emphasise the need for continued effort to develop sound rehabilitation technologies to support re-vegetation and transformation of this disturbed land to a new beneficial condition (Sheoran et al 2010;Limpitlaw and Briel 2015;Weyer et al 2017). Biological rehabilitation has become the strategy of choice and is considered to be economic, safe, more energy efficient and environmentally compatible, and potentially capable of providing a means to convert coal discard to ash and sulphurfree products of value (Reich-Walber et al 1997;Klein et al 2001;Hofrichter and Fakoussa 2001;Machnikowska et al 2002;Sekhohola et al 2013;Cowan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Natural risk sources fall within 7 types: geology, soils, topography, vegetation, hydrology, climate, and land cover. These types conform with the “environmental domain evaluative criteria” defined by Weyer et al (), who emphasized their importance as foundation rehabilitation factors. They influence the potential for rehabilitation failures as well as opportunities because they determine the long‐term viability of land for sufficient ecosystem restoration and are important for building a landscape from the bottom up.…”
Section: Framework Developmentmentioning
confidence: 74%
“…Despite being advocated, rehabilitation risk assessment is however conducted with minimum requirements being met. Weyer et al () found that guidelines and consultants’ approval reports for rehabilitation of surface‐strip coal mines in South Africa and Australia fall between vulnerable and adequate but are not yet resilient. Information is gathered but seldom analyzed, with limited integration and rehabilitation risk determination.…”
Section: Introductionmentioning
confidence: 99%
“…Land devastation in coal mining sites is well documented and emphasizes the need to invest focused effort in developing sound rehabilitation technologies [ 98 , 99 ]. Various traditional chemical approaches have been proposed to restore contaminated mining soils.…”
Section: Bioremediation Of Contaminated Sites By Native Microorganismsmentioning
confidence: 99%